1997
DOI: 10.1176/ajp.154.6.766
|View full text |Cite
|
Sign up to set email alerts
|

Panic disorder and quality of life: variables predictive of functional impairment

Abstract: P anic attacks are highly prevalent in the United States (1), and 5%-8% of patients who present to primary care suffer from panic disorder; many more have infrequent panic attacks (2). People with panic attacks have a higher degree of functional disability than subjects without panic attacks (3). Panic disorder patients tend to be high users of health care services (3, 4), and they perceive their physical and emotional health to be much worse than comparison subjects (3, 5). They are also at higher risk for su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(11 citation statements)
references
References 30 publications
(23 reference statements)
1
10
0
Order By: Relevance
“…Reduced quality of life has been associated with various psychiatric disorders in children and adolescents (Bastiaansen, Koot, Bongers, Varni, & Verhulst, 2004). Studies with adults have shown that individuals with anxiety disorders, including social phobia and specific phobia, report lower levels of life satisfaction than their normal counterparts (see Bech & Angst, 1996; Hollifield et al, 1997; Mogotsi et al, 2000). …”
Section: Methodsmentioning
confidence: 99%
“…Reduced quality of life has been associated with various psychiatric disorders in children and adolescents (Bastiaansen, Koot, Bongers, Varni, & Verhulst, 2004). Studies with adults have shown that individuals with anxiety disorders, including social phobia and specific phobia, report lower levels of life satisfaction than their normal counterparts (see Bech & Angst, 1996; Hollifield et al, 1997; Mogotsi et al, 2000). …”
Section: Methodsmentioning
confidence: 99%
“…Recent estimates suggest that 3.7% of people will meet criteria for PD and 1.1% for PDA in their lifetime (Kessler et al, 2006). PD/PDA is associated with significant impairment in quality of life and role functioning (Hollifield et al, 1997; Stein, et al, 2005). Moreover, PD/PDA is associated with increased healthcare utilization (Rief, Martin, Klaiberg, & BrĂ€hler, 2005), decreased productivity in the form of increased disability (Kouzis & Eaton, 1994), and missed work days (Stein et al, 2005).…”
mentioning
confidence: 99%
“…And a smaller clinical study with 61 patients demonstrated that the presence of depression is a risk factor for worse quality of life amongst patients with panic disorder [7]. …”
Section: Introductionmentioning
confidence: 99%